Immunomodulatory Effect of Pregnancy on Leukocyte Populations in Patients With Multiple Sclerosis: A Comparison of Peripheral Blood and Decidual Placental Tissue - Spadaro, Michela; Martire, Serena; Marozio, Luca; Mastromauro, Daniela; Montanari, Elena; Perga, Simona; Montarolo, Francesca; Brescia, Federica; Balbo, Alessia; Botta, Giovanni; Benedetto, Chiara; Bertolotto, Antonio (Frontiers in Immunology, 2019)
Pregnancy is a naturally occurring disease modifier of multiple sclerosis (MS) associated with a substantial reduction in relapse rate. To date, attempts to explain this phenomenon have focused on systemic maternal immune cell composition, with contradictory results. To address this matter, we compared the immunomodulatory effects of pregnancy on five leukocyte populations (i.e. CD4+ and CD8+ T cells, CD4+CD127-CD25high regulatory T cells, CD56brightCD16- NK cells and CD14+CD163+ monocytes) in peripheral blood from different cohorts of MS patients and healthy women at different times of gestation, as well as in decidual samples from the placenta of MS patients and healthy women collected after delivery. For the first time to our knowledge, we observed that the frequency of these cell populations in the decidua is not different between MS patients and healthy women, suggesting that a physiological immune regulation may occur at the fetal-maternal interface. In peripheral blood, however, contrary to healthy women, in MS patients cell frequencies were not significantly altered by gestation. In particular, CD8+ T cells did not show differences between groups. CD4+ T cells were higher in non-pregnant MS compared to healthy women, while during pregnancy they remained constant in MS and increased in healthy women. Regulatory T cells were higher in non-pregnant controls compared to MS women, while the difference was reduced during gestation due to the decrease of regulatory T cell levels in healthy women. CD14+CD163+ monocytes did not show differences between groups. CD56brightCD16- NK cells were not significantly different in non-pregnant MS compared to controls and increased in healthy women during gestation. In conclusion, our findings support the hypothesis that disease amelioration in MS patients during pregnancy may be due to a modulation of the immune cells functional activity rather than their frequency. Further studies exploring functional changes of these cells would be crucial to bring light into the complex mechanisms of pregnancy-induced tolerance and autoimmunity overall.